Elastisitas Penyerapan Tenaga Kerja Di Provinsi Sumatera Selatan - Anton Trianto (Akuisisi: Jurnal Akuntansi, 2017)
This study aims to analyze the elasticity of employment in the Province of South Sumatra during the period 2011-2015. The calculation of elasticity of labor absorption is obtained from the comparison between the percentage of labor growth to the percentage of economic growth. The data used are secondary data that is the growth of labour and the growth of South Sumatra’s GDP. Elasticity ofemployment  is used to see how big the response changes in the amount of labor that occurs due to economic growth. The results showed that during the period 2011-2015 the elasticity of employment of South Sumatra Province more in inelastic category, except in year 2013 the category is elastic. This means that economic growth has less responsive to stimulate the increasing number of workers. The percentage of employment growth is less than the percentage of economic growth. In addition, economic growth has not been consistent to be one of the factors triggering stable employment in several districts / cities in South Sumatra. Keywords: Economic Growth, Employment Absorption, Elasticity of employment